THE INFECTION EFFECT OF STRAIN H37Rv MYCOBACTERIUM TUBERCULOSIS ON APOPTOSIS OF MICE’S NEURON CELL BRAIN (MUS MUSCULUS) - Kaspia, Rima Nor; Hidayati, Dwi Yuni Nur; Widayati, Aris (Malang Neurology Journal, 2016)
Background. Ischemia on the cells and the lack of supply of glucose, will trigger a Ca2 + influx into the cell and increased expression of glutamate. Result in mitochondrial Ca2 + Influx be "overloaded". Glucose metabolism then switched to the anaerobic process that makes ATP increasingly depleted and there acidosis. This situation makes the neuron cell apoptosis triggered to occur. Apoptosis is programmed cell death. Neuron cell apoptosis is thought to have a strong connection to the tuberculosis infection in the brain.Objective. To determine the number of cells undergoing apoptosis neurons in brain tissue of mice.Methods. This study is a semiquantitative by comparing the number of cells undergoing apoptosis neurons in the three groups of samples. Observations apoptosis of neuronal cells in the brain tissue of mice was conducted using TUNEL staining technique (terminal deoxynucleotidyl transferase dUTP nick end labeling) are seen in a microscope with a magnification of 1000x.Results. The results showed that neuronal cells undergo apoptosis in brain tissue infected with M.tb for 8 and 16 weeks were marked with brown color in the cell nucleus. Neuron cell apoptosis were observed at M.tb-infected brain tissue for 16 weeks.Conclusion. The longer the M.tb infection can affect the increase in the number of neuronal cell apoptosis.